Investigation of different levels of cholecalciferol and its metabolite in calcium and phosphorus deficient diets on growth performance, tibia bone ash and development of tibial dyschondroplasia in broilers - Landy, Nasir; Kheiri, Farshid; Faghani, Mostafa; Bahadoran, Ramin (Acta Scientiarum. Animal Sciences, 2020)
This experiment was conducted to examine the effects of 1-α(OH)D3 alone or in combination with different levels of cholecalciferol on performance, and tibia parameters of one-d–old male broilers fed a tibial dyschondroplasia (TD)-inducing diet. A total of three hundred male broilers were randomly allocated to 5 treatment groups with 4 replicates. The dietary treatments consisted of TD inducing diet, TD inducing diet supplemented with 5 μg per kg of 1-α(OH)D3; TD inducing diet supplemented with 5 μg per kg of 1-α(OH)D3 and 1,500; 3,000 or 5,000 IU cholecalciferol kg-1 of diet. At 42 d of age, broiler chickens fed diets containing 1-α(OH)D3 and 1,500 IU cholecalciferol kg-1 of diet had higher body weight (p < 0.05). In the complete experimental period the best FCR and the highest daily weight gain were obtained in broilers supplemented with 1-α(OH)D3 and 1,500 IU cholecalciferol kg-1 of diet. Broilers supplemented with 1-α(OH)D3 and 1,500 IU cholecalciferol kg-1 of diet had significantly lower incidence and severity of TD in comparison with other groups. In conclusion, the results indicated that the supplementation of 1-α(OH)D3 in combination of 1,500 IU cholecalciferol kg-1 of diet could maximize tibia bone ash, performance and prevent TD in broilers fed TD inducing diet.